Sex Trafficking of Young Girls in Lima, Peru : Practice, Policy and Protection - Novak, Lauren (My University, 2010)
Every nation in the world is affected by the modern day form of slavery, human trafficking. Although slavery is illegal in virtually every country in the world, there are more slaves today than at any point in human history. It is estimated that there are currently 27 million victims of human trafficking and 50% of those victims are minors. The country of Peru is no exception to this growing trend. This investigation specially addresses the problem of all types of trafficking within Peru in the literature review and the problem of the sex trafficking of young girls within the city of Lima, Peru from field research.
Child Sex Trafficking in Peru : Policy, Practice, and Protection
Color poster with text.
Keywords: Human trafficking--Peru; Human trafficking--Peru--Sociological aspects; Human trafficking--Government policy--Peru; Posters